Effect of Embelin Against Lipopolysaccharide‐induced Sickness Behaviour in Mice. (18th February 2016) - Shaikh, Ashique; Dhadde, Shivsharan B.; Durg, Sharanbasappa; Veerapur, V. P.; Badami, S.; Thippeswamy, B. S.; Patil, Jagadevappa S.
Abstract : Sickness behaviour is a coordinated set of adaptive behavioural changes that develop in ill individuals during the course of an infection. It is relevant to understanding depression and some aspects of the suffering that in cancer. Embelin has been reported to possess antiinflammatory, neuroprotective and anxiolytic assets and has been shown to inhibit nuclear factor κB pathway and cytokine production. The present study was undertaken to investigate the effect of embelin isolated from Embelia ribes Burm in lipopolysaccharide (LPS)‐induced sickness behaviour in mice. Adult male Swiss albino mice were pre‐treated with embelin (10 and 20 mg/kg, p.o.) or dexamethasone (1 mg/kg, i.p.) for 3 days and then challenged with LPS (400 µg/kg, i.p.). At different time intervals of post‐LPS challenge, sickness behaviour was evaluated in the animals by battery of behavioural tests (plus maze, open field, light–dark box, forced swim, social behaviour assessment, sucrose preference and food and water intake). Levels of oxidative stress makers (reduced glutathione and lipid peroxidation) in mice brain were also analysed. LPS induced behavioural alterations, anhedonia and anorexia, in mice. Pre‐treatment with embelin attenuated behavioural changes induced by LPS. In addition, embelin prevented anhedonia, anorexia and ameliorated brain oxidative stress markers. The experimental outcomes of the present study demonstrated protective effect of embelin in LPS‐induced sickness behaviour in mice. Copyright © 2016 John Wiley & Sons, Ltd.